2018
DOI: 10.1111/cas.13633
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Blockade of ONECUT2 expression in ovarian cancer inhibited tumor cell proliferation, migration, invasion and angiogenesis

Abstract: One cut homeobox 2 (ONECUT2 or OC‐2) is a newly discovered transcription factor. Aberrant expression of OC‐2 is closely related to cell proliferation, migration, invasion, and angiogenesis. In this study, we found that OC‐2 expression was upregulated in ovarian adenocarcinoma cells, by Western blot analysis. The results of immunohistochemistry showed that the expression of OC‐2 was also increased in malignant ovarian cancer tissue. In order to explore the role of OC‐2 in the development of ovarian cancer, siRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…ONECUT2 is involved in liver, pancreas, and nervous-system development 45 and has recently been proposed as a regulator of tumor growth in ovarian cancer (MIM: 167000). 46 Finally, our study reveals that archaic introgression has impacted enhancers in a tissue-specific manner, reflecting either high human-Neanderthal differentiation, as observed in T cell enhancers, or increased archaic introgression, as detected in AdMSCs. Interestingly, the AdMSC enhancers impacted by archaic introgression interact preferentially with genes involved in the regulation of adipocyte differentiation and adipogenesis.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…ONECUT2 is involved in liver, pancreas, and nervous-system development 45 and has recently been proposed as a regulator of tumor growth in ovarian cancer (MIM: 167000). 46 Finally, our study reveals that archaic introgression has impacted enhancers in a tissue-specific manner, reflecting either high human-Neanderthal differentiation, as observed in T cell enhancers, or increased archaic introgression, as detected in AdMSCs. Interestingly, the AdMSC enhancers impacted by archaic introgression interact preferentially with genes involved in the regulation of adipocyte differentiation and adipogenesis.…”
mentioning
confidence: 67%
“…36 We found that background selection correlated with a lower rate of archaic introgression (r ¼ À0.049, p value < 10 À15 , Figure 4B), consistent with previous findings, 1,2 but also correlated with increased local divergence (r ¼ 0.22, p value < 10 À20 , Figure 4C) and reduced density of both common variants and fixed differences (r ¼ À0. 46 and À0.05, respectively, p value < 5 3 10 À20 , Figure S4). We also found that negative selection and recombination rate correlated with both divergence and introgression, even after we adjusted for background selection ( Figure S5).…”
mentioning
confidence: 91%
“…The ONECUT transcription factors, including OC2 , are evolutionarily conserved proteins that play a role in the development of the liver, pancreas and neuronal system . Although a role for OC2 in cancer is not well defined, it was recently reported that OC2 was aberrantly upregulated in a variety of cancer types, including hepatocellular carcinoma, prostate cancer, colorectal cancer and ovarian cancer . Recently, it has been proposed that during the multistep development human tumors acquire six hallmarks of cancer, including sustaining proliferative signaling, evading growth suppressors, resisting cell death, enabling replicative immortality, inducing angiogenesis and activating invasion and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…RIG‐I‐LIKE receptor signaling pathway has a high impact on cell growth, migration, and invasion of tumor . VEGF signaling pathway is involved in angiogenesis, migration and invasion and of OC …”
Section: Discussionmentioning
confidence: 99%